Studies on the impact of key environmental variables on kashmir catfish (Glyptothorax kashmirensis Hora, 1923) distribution and abundance in Azad Jammu and Kashmir, Pakistan - Nagina Gilani; MUHAMMAD RAFIQUE; Shamim Akhter; Huma Qureshi; Ahmad Shoaib; Shakeel Ahmad (Kuwait Journal of Science)
Kashmir catfish (Glyptothorax kashmirensis) is IUCN declared critically endangered freshwater fish inhabiting Azad Jammu and Kashmir (AJK). Limited data is available on ecological patterns of the species, therefore; study was conducted to investigate its habitat ecology at different sites in Jhelum (Gucha, Subri, Ambor, and Rahra) and Poonch river (Jawra, Hajira, Tata Pani and Barali). The distribution range of Kashmir catfish extended upstream from Kohala to Chakothi in Jhelum river and from Gulpur to Madalpur in Poonch river. It inhabits riverbed mixed with small gravel and coarse sand (diameter 2 mm -50 mm) in river depth range of 0.2-0.5 m; frequently in upper reaches of river with low water flow (300 comics m/sec). Maximum specimens were observed in Gucha (Jhelum) and Jawra (Poonch) in summer months (July-September). Principle correspondence analysis and canonical correspondence analysis were used to examine the association of environmental variables (water flow, temperature, dissolved oxygen, pH, turbidity) with species abundance which indicated that the species occurrence was highly correlated with these factors. Present work explains the relationship of species relative abundance and physicochemical features of the species, which may assist species conservation.